B2B price optimization analytics - Higbie, Jon (Henry Stewart Talks, 2009)
Applications within many industries, Typical B2B sales process with pricing analytics, Responsibilities of the pricing analytics team, Determining optical pricing quotes, Price optimization process, Data requirements, Computing the market response units, Considerations for determining the contribution function, Determining the optimal quote price